The role of modulated IR radiometry measurements in the characterization of Zr-O-N thin films - Macedo, Francisco (2009)
This work is devoted to the investigation of relevant thermal transport parameters of multifunctional ZrOxNy thin films, prepared in strict controlled conditions. Composition and structural characterizations revealed the existence of two different types of films, with a structural change from fcc ZrN to Zr3N4-type. Modulated IR radiometry was used to screen out these internal changes, and also to prove its importance and application viability within complicate systems such as thin films. The thermal diffusion time of the coatings and the ratio of the thermal effusivities coating-to-substrate were directly determined. Empirical correlations between processing conditions, the films’ composition and structure, and thermal transport properties were found.